PANDEMIC TO ENDEMIC propositions for the future. - Divekar, Rajiv; Chopra, Komal; Chitranshi, Jaya.; Mehendale, Smita ([S.l.] : ROUTLEDGE, 2024)
The pandemic wave of Covid 19 made many organizations in different sectors rethink their business strategy. The pandemic wave soon became an endemic and the organizations adapted themselves to the new ways of doing business. Endemic situation indicates that the Covid virus is here to stay but with limited impact. The book provides deeper research on how organizations adapted themselves to the post Covid situation and how they look at the future. The book covers studies from the areas of marketing, finance, human resource, operations, healthcare and education.
Keywords: Management; COVID-19 Pandemic, 2020- -- Influence; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Management